2008
DOI: 10.1146/annurev.earth.36.031207.124120
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamic Significance of Seismic Anisotropy of the Upper Mantle: New Insights from Laboratory Studies

Abstract: Seismic anisotropy is caused mainly by the lattice-preferred orientation of anisotropic minerals. Major breakthroughs have occurred in the study of lattice-preferred orientation in olivine during the past ∼10 years through large-strain, shear deformation experiments at high pressures. The role of water as well as stress, temperature, pressure, and partial melting has been addressed. The influence of water is large, and new results require major modifications to the geodynamic interpretation of seismic anisotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
711
3
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 686 publications
(733 citation statements)
references
References 91 publications
13
711
3
6
Order By: Relevance
“…Even if it would not be seismically visible by itself, the presence of hollandite in subducting slabs would release some of the constraints that are imposed on the lattice-preferred orientation of olivine and pyroxene crystals (Mainprice et al, 2000, Karato et al, 2008 to explain the seismic observations. Thus our results show that further mineralogical and seismic models of K-rich regions of the upper mantle should also consider the seismic signature of hollandite and of its ferroelastic transition.…”
Section: Resultsmentioning
confidence: 99%
“…Even if it would not be seismically visible by itself, the presence of hollandite in subducting slabs would release some of the constraints that are imposed on the lattice-preferred orientation of olivine and pyroxene crystals (Mainprice et al, 2000, Karato et al, 2008 to explain the seismic observations. Thus our results show that further mineralogical and seismic models of K-rich regions of the upper mantle should also consider the seismic signature of hollandite and of its ferroelastic transition.…”
Section: Resultsmentioning
confidence: 99%
“…This configuration was known as olivine type-B, whereas the relationship of dry olivine is type-A. Typically, type-A olivine is found in regions of low water content, relatively small amounts of stresses and high temperatures, while type-B olivine is characteristic of enriched water settings, high stresses and low temperature (Jung & Karato 2001;Karato et al 2008;Long 2009a). In subduction zones, the mantle wedge tip frequently meets the conditions required for the existence of type-B olivine, whereas type-A (or similar) is found throughout the mantle wedge core (Kneller et al 2005).…”
Section: Upper Mantlementioning
confidence: 99%
“…The kernels are calculated with respect to a homogeneous background model with a horizontal axis of symmetry; for further details, see 3 Linking Shear Wave Splitting to Mantle Processes Seismic anisotropy in the Earth's mantle is a consequence of deformation, whether through LPO or SPO, and it is this link between mantle flow and the geometry and strength of anisotropy that drives much of the scientific interest in shear wave splitting as a geophysical technique. Recent overviews of experimental mineral physics results relating to mantle anisotropy have been published by Mainprice (2007), Karato et al (2008) (for upper mantle anisotropy), and Yamazaki and Karato (2007) (for D 00 anisotropy), and for a more detailed review of the mineral physics literature we refer the reader to these publications. Here, we provide a brief overview of the experimental constraints on the relationship between deformation and the resulting anisotropy and a general summary of recent advances relevant to the interpretation of shear wave splitting measurements.…”
Section: Inverse Modeling: Shear Wave Splitting Tomographymentioning
confidence: 99%
“…Studies by Katayama et al (2004), Jung et al (2006), and Katayama and Karato (2006) mapped out the occurrence of Surv Geophys (2009) 30:407-461 429 five different olivine fabric types (the original A-type plus B-, C-, D-, and E-types). Karato et al (2008) suggested that that the asthenospheric upper mantle may generally be dominated by E-or C-type olivine rather than the traditionally assumed A-type. Natural occurrences of each of the olivine fabric types recognized in the laboratory have been identified, notably B-type fabric from convergent boundaries (e.g., Mizukami et al 2004;Skemer et al 2006) and C-type fabric from deep mantle samples (see, e.g., Katayama and Karato 2006).…”
Section: The Upper Mantlementioning
confidence: 99%
See 1 more Smart Citation